2019
DOI: 10.1002/smtd.201900378
|View full text |Cite
|
Sign up to set email alerts
|

Disinfection of Infected Root Canals: Nanosilver Has Good Potential

Abstract: Bacterial elimination is the key to the treatment of periapical periodontitis. However, existing root canal disinfectants have not fully met this requirement. Here, a new disinfectant candidate, nanosilver, is provided and its efficacy against root canal infection is analyzed. Compared to calcium hydroxide, the nanosilver, which is evenly loaded into the poly(lactic‐co‐glycolic acid) carrier, shows excellent bactericidal activity against free‐living Enterococcus faecalis, stable‐phase E. faecalis biofilm, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Noncanonical inflammasomes may also participate in the pathogenesis of periapical bone loss. The increased expression of caspase-1 and caspase-11 in RAW264.7 cells treated with LPS was found to be significantly reduced by nanosilver, and this decreased inflammasome activity may contribute to the alleviation of canine periapical periodontitis progression ( 185 ). In addition, estrogen deficiency can induce activation of the NLRP3/caspase-1/IL-1β axis and aggravate periapical bone loss in postmenopausal patients and ovariectomized rats with periapical periodontitis ( 267 ).…”
Section: Inflammasomes In Inflammatory Osteolysis Of the Alveolar Bone And Jawsmentioning
confidence: 99%
“…Noncanonical inflammasomes may also participate in the pathogenesis of periapical bone loss. The increased expression of caspase-1 and caspase-11 in RAW264.7 cells treated with LPS was found to be significantly reduced by nanosilver, and this decreased inflammasome activity may contribute to the alleviation of canine periapical periodontitis progression ( 185 ). In addition, estrogen deficiency can induce activation of the NLRP3/caspase-1/IL-1β axis and aggravate periapical bone loss in postmenopausal patients and ovariectomized rats with periapical periodontitis ( 267 ).…”
Section: Inflammasomes In Inflammatory Osteolysis Of the Alveolar Bone And Jawsmentioning
confidence: 99%
“…Caspase inhibition can be classified into direct and indirect approaches. Direct inhibitors of caspase include caspase pan inhibitor (Z‐VAD‐FMK), 104 caspase‐1 inhibitors (Ac‐YVAD‐CHO, Ac‐YVAD‐CMK, VX765), 67,68,81,93 caspase‐3 inhibitor (Ac‐DEVD‐FMK), 21 caspase‐4 inhibitor (Z‐LEVD‐FMK), 104 and caspase‐1 and caspase‐11 common inhibitor (nanosilver) 125 . Indirect inhibitors of caspase‐1 consist of peroxisome proliferator‐activated receptor γ (PPARγ) activator (Arhalofenate), 126 and Hedgehog inhibitor (GANT‐61) plus indomethacin 127 …”
Section: Targeting Strategies Of Pyroptosis In Inflammatory Bone Dise...mentioning
confidence: 99%
“…One study demonstrated that adding nanosilver to the particle-poly(lactic-co-glycolic acid) (PLGA) carrier showed not only great bactericidal activity but also excellent biocompatibility. 125 What is more, recent studies revealed that combining EVs with miRNAs could effectively block the pyroptosis-related signaling pathway and alleviate inflammatory conditions. 142,149 Thus, extracellular vesicles (including exosomes and microvesicles), which might be a potential strategy for treating inflammatory diseases, should be extensively explored further.…”
Section: Caspase Direct Inhibitorsmentioning
confidence: 99%
See 2 more Smart Citations